Effect of Arthritic Synovial Fluids on the Expression of Immunomodulatory Factors by Mesenchymal Stem Cells: An Explorative in vitro Study - Leijs, Maarten J.; Van Buul, Gerben M.; Lubberts, Erik; Bos, Pieter K.; Verhaar, Jan A.; Hoogduijn, Martin J.; van Osch, Gerjo J. (Frontiers in Immunology, 2012)
Background: In diseased joints, the catabolic environment results in progressive joint damage. Mesenchymal stem cells (MSCs) can have immunomodulatory effect by secreting anti-inflammatory factors. To exert these effects, MSCs need to be triggered by pro-inflammatory cytokines. To explore the potential of MSCs as a treatment for diseased joints, we studied the effect of synovial fluid (SF) from donors with different joint diseases and donors without joint pathology on the immunomodulatory capacities of human MSCs in vitro. We hypothesized that SF of diseased joints influences the immunomodulatory effects of MSCs. Materials & Methods: MSCs were cultured in medium with SF of six osteoarthritis (OA) or six rheumatoid arthritis (RA) donors and three donors without joint pathology were used as control. Gene expressions of IL-6, HGF, TNFa, TGFb1 and indoleamine 2,3-dioxygenase (IDO) were analysed. L-kynurenine concentration in conditioned medium (CM) by MSCs with SF was determined as a measure of IDO activity by MSCs. Furthermore, the effect of CM with SF on proliferation of activated lymphocytes was analysed. Results: Addition of SF significantly up-regulated the mRNA expression of IL-6 and IDO in MSCs. SF(OA) induced significantly higher expression of IDO than SF(control), although no difference in IDO activity of the MSCs could be shown with a L-kynurenine assay. Medium conditioned by MSCs with SF(OA or RA) suppressed activated lymphocyte proliferation in vitro more than medium conditioned by MSCs without SF or with SF(control). Discussion: SF can influence the expression of genes involved in immunomodulation by MSCs and the effect on lymphocyte proliferation. We found indications for disease-specific differences between SFs but the variation between donors, even within one disease group was high. These data warrant further research to examine the potential application of MSC therapy in arthritic joints.